Addressing Climate Change in Transport : Volume 2 : Pathway to Resilient Transport - Oh, Jung Eun (World Bank, Hanoi, 2019)
Climate change is set to have profound effects on Vietnam’s development. With nearly sixty percent of its land area and seventy percent of population at risk of multiple natural hazards, Vietnam globally is among the most vulnerable countries to both chronic and extreme events. At the same time, as Vietnam’s economy grows, the country is becoming a significant emitter of greenhouse gases. While Vietnam’s absolute volume of emissions is still small compared to that of larger and richer countries, emissions are growing rapidly and disproportionate to its economy size. The transport sector plays a critical role in these recent trends. This study aims to set out a vision and strategy for climate-smart transport, in order to minimize the carbon footprint of the sector while ensuring its resilience against future risks. The analytical findings and recommendations are presented in two volumes of the report. The first volume provides how Vietnam can reduce its carbon emissions by employing a mix of diverse policies and investments, under varying levels of ambition and resources. The second volume provides a methodological framework to analyze network criticality and vulnerability, and to prioritize investments to enhance resilience.